2009
DOI: 10.1002/jcb.22387
|View full text |Cite
|
Sign up to set email alerts
|

The effect of receptor protein tyrosine phosphatase kappa on the change of cell adhesion and proliferation induced by N‐acetylglucosaminyltransferase V

Abstract: N-acetylglucosaminyltransferase V (GnT-V) has been reported to be positively associated with tumor progression, but its mechanism still remains unknown. In the present study, we found that GnT-V overexpression not only changed the glycosylation of receptor protein tyrosine phosphatase kappa (RPTPkappa) but also decreased its protein level. Moreover, GnT-V overexpression decreased cell calcium-independent adhesion and increased the tyrosine phosphorylation level of beta-catenin, in which RPTPkappa played an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It was also reported that transcription levels of mgat4b , and mgat5 were increased in mice with HCC [9] . Recently, further analysis revealed that mgat5 could partially decrease cell adhesion and promote cell proliferation through RPTPκ [10] .…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that transcription levels of mgat4b , and mgat5 were increased in mice with HCC [9] . Recently, further analysis revealed that mgat5 could partially decrease cell adhesion and promote cell proliferation through RPTPκ [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of glycosylation on RPTPs could affect their membrane retention level and change their phosphatase activity [20], [21]. We detected the in situ PTPRT expression in GnT-V cells and Mock cells.…”
Section: Resultsmentioning
confidence: 97%
“…The effect of aberrant N-glycosylation in PTPRT molecule on its function has not been well defined. PTPRK, an N-linked glycoprotein, has been reported as a novel substrate of GnT-V [19], [20]. In this study, we are interested in exploring whether GnT-V overexpression could affect PTPRT N-glycosylation and increase the amount of PTPRT at cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PTPRF (LAR) is cleaved intracellularly into two subunits[ 11 ]. Proteolytic processing of other members of the PTPR family has been reported [ 12 15 ]. Among these, it is known that three isoforms of PTPRZ, the only other member of class V PTPRs beside PTPRG, are generated by alternative splicing from a single Ptprz gene in the rat [ 16 ].…”
Section: Introductionmentioning
confidence: 99%